Networked Growth - LEUNG, Hing-Man (Institutional Knowledge at Singapore Management University, 2002)
This paper searches for a new growth engine in the new Info-Tech economy. IT-network effects are incorporated into Romer’s (1990) framework. Network effects support long-term steady state growth in per capita variables even without innovation, and growth rate increases with network externalities. Networked growth is sub-optimal, so should we break up an IT monopoly? To answer this we compare monopoly, Cournot and Bertrand set-ups. Cournot always ranks last socially, but Bertrand can be superior to monopoly if network effects are strong. When network interacts with Romer’s endogenous innovation, growth rate increases, probably by up to a percentage point per year.